Conference conclusions: shaping the future of food safety, together. (June 2016) - Robinson, Tobin; Germini, Andrea; Deluyker, Hubert; Hardy, Anthony; Liem, Djien
Abstract: The EFSA 2nd Scientific Conference 'Shaping the Future of Food Safety, Together' gathered an international audience composed of scientists, risk assessors, risk managers, as well as non‐governmental organisations and industry representatives. This article summarises the final plenary session where a panel was asked to draw out overall impressions and conclusions for the EFSA to take away for its strategic planning into the future. The main conclusions of the conference are presented under five major themes. With new methodologies, technologies, big data and the increased societal demand for enhanced engagement in the risk assessment process, there is a clear need to maintain levels of expertise from traditional areas and to consider the inclusion of new areas and sources of expertise to perform scientific assessments. Academia, industry, research and regulatory science should work together to achieve this goal. As science progresses at pace, the continued development of assessment methodologies to deal with increasingly complex assessment questions is necessary, as is the need for applied research to underpin the support to policy development that EFSA provides. Greater collaboration is needed to reach agreement on best methods and practices for scientific assessment not just internationally, but also, equally importantly, across legislative areas and scientific disciplines, and in consultation with society at large. The communication of complex science, including important concepts such as uncertainty and risk perception, is not a trivial task, and must be integrated into the scientific process. As such, the relationship between risk assessment and risk management must continue to mature, remaining close, yet independent.